University students' e-waste disposal and recycling behavior: a cross-cultural study using an integrated psychological model - Trinh, Duy Duc; Sakurai, Ryo (Frontiers in Sustainability, 2025)
The escalating global volume of electronic waste (e-waste), coupled with low recycling rates, poses a significant environmental and public health challenge. This necessitates a deeper understanding of individual disposal behaviors, as e-waste is predominantly a problem due to the low level of individual engagement in the appropriate disposal of these materials. Individual engagement in pro-environmental behavior is as essential as technology implementation in managing the e-waste crisis, as changes in individual behavior could significantly influence environmental outcomes. This study takes a robust cross-cultural approach, surveying a sample of 2,450 university students, including 950 from Vietnam and 1,500 from Japan, who are frequent users of personal electronic devices and generally have high environmental awareness. By integrating the value-belief-norm model, valence theory, and drivers from reverse logistics concepts, this research explores how students in two distinct cultural contexts assess and act regarding e-waste disposal and recycling. Furthermore, this research pioneers the use of the Environmental Portrait Value Questionnaire to measure values associated with environmental actions and attitudes in e-waste recycling. Using Structural Equation Modeling (SEM), the findings demonstrate that recycling inclinations were influenced by personal norms, regulation drivers, economic drivers, ascription of responsibility, and perceived benefits and risks toward e-waste recycling. Among them, regulation drivers had the largest impact in both countries (β = 0.331, p < 0.001, Vietnam; β = 0.344, p < 0.001, Japan). Furthermore, the model is promising for adoption in the field of e-waste recycling in other countries, as indicated by its good model fit (i.e., the root mean square error of approximation [RMSEA] < 0.08; NFI, CFI, TLI > 0.9). These discoveries would be helpful for policymakers and researchers in both countries aiming to understand the factors driving students' decisions to recycle e-waste.